Comparative evaluation of lethal outcome prediction methods in severely burned patients - O. O. Zavorotniy; E. V. Zinoviev; V. G. Volkov; D. V. Kostyakov; D. H. Halipaeva; A. V. Semiglazov; T. Z. Gogohiya (Инновационная медицина Кубани)
Background: Regarding burn injury there are many approaches to assessing the possibility of death in severely burned patients. Despite the ease of use and the maximum prevalence of existing models, the assessment of the outcome in each of them is questionable, since the emphasis in different indices is on different indicators, avoiding the overall clinical picture of the disease.Objective: Comparative analysis of the effectiveness of methods for predicting a lethal outcome in patients with extensive skin burns.Material and мethods: Calculated characteristics of known in the literature and widely used Baux rules, Frank index, probit analysis and a new method of logistic regression were obtained and applied to evaluate the results of treatment of 282 adult patients with extensive skin burns, hospitalized in the Department of Anesthesiology and Intensive Care of the Thermal Injuries Unit, Saint-Petersburg I. I. Dzhanelidze Research Institute of Emergency Medicine in the period 2015–2021.Results: During the study a descriptive characteristic of methods for predicting a lethal outcome was obtained. Based on the data obtained, four-field contingency tables were compiled and a comparative analysis of the effectiveness of the models was carried out.Conclusion: Despite the high frequency of use of such forecasting methods as the Baux score, the Frank index and probit analysis in the combustiology practice, the results of the calculation indicate that these methods have low efficiency: the Baux score method accuracy of a lethal outcome prediction is 49.7%, the Frank index method – 41.5%, probit analysis method – 60%. The logistic regression model developed by us showed high efficiency compared to those presented earlier (the accuracy of predicting a lethal outcome was 93%), which gives grounds for recommending it for practical application.